Wind energy engineering : a handbook for onshore and offshore wind turbines - Letcher, T. M. (Academic Press, an imprint of Elsevier, 2023)
Wind Energy Engineering: A Handbook for Onshore and Offshore Wind Turbines, Second Edition continues to be the most advanced, up-to-date and research-focused text on all aspects of wind energy engineering. Covering a wider spectrum of topics in the field of wind turbines (offshore and onshore), this new edition includes new intelligent turbine designs and optimization, current challenges and efficiencies, remote sensing and smart monitoring, and key areas of advancement, such as floating wind turbines. Each chapter includes a research overview with a detailed analysis and new case studies looking at how recent research developments can be applied. Written by some of the most forward-thinking professionals in the field, and giving a complete examination of one of the most promising and efficient sources of renewable energy, this book is an invaluable reference into this cross-disciplinary field for engineers.